BELAJAR SAMBIL BERMAIN KOSA KATA BAHASA INGGRIS PADA SISWA SEKOLAH DASAR: EVALUASI MOTIVASI DAN PENGETAHUAN - Maria Martha Nikijuluw; Theofelia Papasoka; Hendry Izaac Elim; Pieldrie Nanlohy (German für Gesellschaft (J-Gefüge), 2022)
Foreign language skills are needed to be able to compete internationally, so the role of English in education is expected to improve the quality of human resources as one of the pillars of education. Improving the quality of human resources is meant to start earlier, namely for the elementary school students. The Community Service (PkM) activities at elementary schools in central Maluku aims to (a) find out students' motivation in learning English, and (b) find out English knowledge at the elementary school level at the level of words and themes that become students' interest in learning. The results of PkM activities by applying learning while playing methods: word play, short sentences, and sentence dictation (Indonesian sentences, written in English and vice versa) indicate that the majority of students have motivation in learning English, it can be proven through the active role of students in the teaching and learning process and students' enthusiasm in answering questions given by the teacher. While student’s knowledge of English shows that the number of students who could fill in the words in the table according to the number given (50 words in 15-20 minutes) was very minimum (4 pairs from a total of 20 pairs or 20%). Further, students could write words with varied topics/themes. The most popular topics were animals (animals) and colors (colors), and also students were able to write simple Indonesian sentences into English or vice versa.